Vascular Endothelial Growth Factor – Marker for Proliferation in Thyroid Diseases? - Malkomes, P.; Oppermann, E.; Bechstein, W. O.; Holzer, K. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Vascular endothelial growth factor (VEGF) is a critical regulator of angiogenesis and is involved in tumor development. To date, the role of VEGF in benign diseases of the thyroid is not well known. The purpose of the present study is to determine the expression of VEGF and its receptors in primary cultures of human thyrocytes.50 patients with uninodular (n=11), multinodular (n=15), recurrent goiter (n=14) and Graves’ disease (n=10) were enrolled. Nodular and corresponding paranodular tissue was obtained after surgery and investigated. RNA and protein were extracted from primary thyrocyte cultures. PCR, western blot and ELISA were performed to evaluate VEGF isoforms and VEGF receptor 1 and 2.Significantly increased transcription and protein expression of VEGF and its receptors were detected in nodular tissue of uninodular and recurrent goiter compared to the corresponding normal tissue. Active secretion of VEGF by thyrocytes was confirmed by ELISA. In multinodular goiter, no difference could be found between nodular and corresponding paranodular tissue in terms of expression of VEGF or its receptors. Furthermore, we found the highest levels of VEGF and its receptors in tissue obtained from patients with Graves’ disease.Increased expression of VEGF and its receptors might be crucial in the proliferation of thyrocytes and therefore may contribute to the development of goiter and goiter recurrence.
Keywords: VEGF; VEGF receptors 1 and 2; goiter; recurrent; multinodular; Graves’ disease